PERANAN METODE DISKUSI DALAM PEMBENTUKAN KARAKTER MAHASISWA MELALUI MATA KULIAH PENDIDIKAN KEWARGANEGARAAN (PKn) - Saputra, Edi (Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
In the current civics lesson, students often experience boredom and tends to just lecture to simply look for value alone. This is due to the material being taught monotonous, theoretical, cognitive nature, even verbalistic. In the course it appears that the students just come, sit down, shut up and go home and some have fallen asleep. Although the discussion of the methods applied in lectures, but students and lecturers are more likely to lead to the questioning, rarely exchanging information, let alone understanding, not able to analyze and comment on the information that is different, and not many are active but more so the audience, so the ability critical thinking and interpersonal skills difficult to achieve. This resulted in